Software engineering : International Summer Schools, ISSSE 2009-2011, Salerno, Italy. Revised Tutorial Lectures - Ferrucci, Filomena; Lucia, Andrea (Lecture Notes in Computer Science, 2013)
Software engineering is widely recognized as one of the most exciting, stimulating, and profitable research areas, with a significant practical impact on the software industry. Thus, training future generations of software engineering researchers and bridging the gap between academia and industry are vital to the field. The International Summer School on Software Engineering (ISSSE), which started in 2003, aims to contribute both to training future researchers and to facilitating the exchange of knowledge between academia and industry. This volume consists of chapters originating from a number of tutorial lectures given in 2009, 2010, and 2011 at the International Summer School on Software Engineering, ISSSE, held in Salerno, Italy. The volume has been organized into three parts, focusing on software measurement and empirical software engineering, software analysis, and software management. The topics covered include software architectures, software product lines, model driven software engineering, mechatronic systems, aspect oriented software development, agile development processes, empirical software engineering, software maintenance, impact analysis, traceability management, software testing, and search-based software engineering.